Pre-patterning and post-oxidation-crosslinking of Fe(0) particles for a humidity-sensing actuator. Issue 100 (28th November 2019) - Qiu, Xiaxin; Liang, Shumin; Huang, Xinhua; Zhang, Lidong
Abstract : The combination of physical pre-patterning and chemical post-crosslinking strategies enables a humidity-sensing actuator with differential mechanical tensors for controlled interfacial sensitivity. Abstract : We propose a pre-patterning and post-oxidation-crosslinking protocol to prepare a humidity-sensing actuator. Fe(0) particles (FeP) are introduced into a sodium alginate (SA) film under a magnetic field (15 mT) to achieve directional pre-patterning, followed by treatment in hydrochloric acid that oxidates FeP into Fe 2+, and triggers the crosslinking between Fe 2+ and SA, which provides the actuator with differential mechanical tensors and induces controlled response to humidity.